Sastra Sunda dalam Kurun Waktu Tiga Dasawarsa Terakhir - Dian Hendrayana (Jurnal Pendidikan Bahasa dan Sastra, 2022)
Sundanese literature is still being written and read today. Its existence is still supported by discussions and studies, festivals, and performances. In its development, Sundanese literature shows its characteristics periodically through writing techniques, style of expression, and the themes it raises. The purpose of writing this article is to describe the existence of Sundanese literature in the last three decades. The method used is phenomenology and narrative research from Creswell by analyzing events and activities related to Sundanese literary life in the last three decades, as well as observations on Sundanese literary life based on literary works written in Sundanese magazines and Sundanese newspapers, in the 1990s until now. The study of drama literature is carried out on performances that are usually performed by Sundanese theater communities. The data obtained shows that the life of Sundanese literature, namely poetry, prose, and drama is still developing when compared to other regional literature in Indonesia. This can be seen from literary activities, literary performances, and literary prizes.